Faktor Risiko Kejadian HIV/AIDS pada Laki-Laki Seks Laki-Laki di Kota Bukittinggi - Arianti, Fadilla Rahmi; Markolinda, Yessy; Putri, Anggela Pradiva (Universitas Hang Tuah Pekanbaru, 2025)
The group of Men Sex Men (MSM) is 25 times more likely to contract HIV compared to heterosexual adult men. The Bukittinggi City Health Office recorded that MSM constituted the highest key population in 2023, with a total of 573 individuals. HIV/AIDS prevention and control efforts in Bukittinggi City need to be continuously monitored and strengthened, especially given the significant increase in the MSM population in 2023. This study aims to identify the factors influencing HIV/AIDS incidence among Men Who Have Sex with Men (MSM) in Bukittinggi City. The research employs a case-control design, with a sample of 21 HIV-infected MSM as the case group and 42 non-HIV-infected MSM as the control group, using questionnaires as intruments. Data were analyzed using univariate analysis, bivariate analysis with the chi-square test, and multivariate analysis using multiple logistic regression. The results showed that the dominant factors associated with HIV/AIDS incidence were Attitude (p-value = 0.001; OR = 0.019), Peer Influence (p-value = 0.037; OR = 7.993), and Experience of Sexual Violence (p-value = 0.039; OR = 0.141). These findings can serve as a foundation for more holistic and sustainable education and counseling programs that are trauma-sensitive and address risky behaviors as part of the HIV/AIDS response strategy.